The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/jts.2490080409
|View full text |Cite
|
Sign up to set email alerts
|

Change in rape narratives during exposure therapy for posttraumatic stress disorder

Abstract: This paper presents a coding system developed to explore changes in narratives of rape during therapy for posttraumatic stress disorder (PTSD) involving repeated reliving and recounting of the trauma. Relationships between narrative categories hypothesized to be affected by the treatment and treatment outcome were also examined. As hypothesized, narrative length increased from pre- to post-treatment, percentage of actions and dialogue decreased and percentage of thoughts and feelings increased, particularly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
307
3
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 404 publications
(329 citation statements)
references
References 31 publications
16
307
3
3
Order By: Relevance
“…Moreover, smaller HR increases during trauma recall were found to predict poorer recovery in PTSD symptoms six months later. These findings of lowered cardiovascular reactivity are reminiscent of the proposal that limited emotional arousal impedes the processing of traumatic memories (Foa, Molnar, & Cashman, 1995). …”
Section: Heart Rate As An Index Of Emotional Arousalmentioning
confidence: 58%
“…Moreover, smaller HR increases during trauma recall were found to predict poorer recovery in PTSD symptoms six months later. These findings of lowered cardiovascular reactivity are reminiscent of the proposal that limited emotional arousal impedes the processing of traumatic memories (Foa, Molnar, & Cashman, 1995). …”
Section: Heart Rate As An Index Of Emotional Arousalmentioning
confidence: 58%
“…The Posttraumatic Stress Diagnostic Scale (PDS; Foa et al 234 ), a 49-item self-reported measure, aids in PTSD diagnosis and symptom severity, with items that parallel DSM-IV criteria 235,236 ) is designed as a screening instrument for use with health-care seeking populations It provides information on perceived symptoms of (a) depression, (b) anxiety, (c) somatic complaints, and (d) psychological distress…”
Section: Pdsmentioning
confidence: 99%
“…These results suggest that the processes of organizing and articulating the traumatic memories are involved in post-trauma recovery. The hypothesis that narrative organization is related to recovery was also supported in a treatment study conducted by Foa et al (1995). In this study the content of the initial and last narrative recounted by sexual and non-sexual assault victims during exposure therapy was analysed using a coding system developed speci®cally for the study.…”
mentioning
confidence: 99%